KEDUDUKAN HUKUM PERKAWINAN ADAT DAYAK LUNDAYEH DALAM HUKUM PERKAWINAN NASIONAL - Pasri Bilung (Universitas Borneo Tarakan, 2020)
AbstractThe procedure of marriage which is carried out in a customary manner and has existed before the State of Indonesia was established, as carried out by the Lundayeh Dayak community and until now is still maintained as a local culture of ancestral heritage is a tradition that is still highly upheld. Unification in the field of marital law through the establishment of Law No. 1 of 1974 has legal consequences for marital arrangements in Indonesia. So that it raises problems with the implementation of the marriage which is only carried out by customary Dayak Lundayeh.The type of this research is normative juridical research, namely legal research to find the rule of law, legal principles and legal doctrine to answer the issue of juridical review of customary marriage and its legal consequences.The results of the study indicate that the customary marriage law is a legal rule that regulates the forms of marriage, how to apply, marriage ceremonies and the termination of marriage. Based on the provisions of the regulations stipulated in Law No. 1 of 1974, marriages which are only carried out by Lundayeh customary without religious marriage are not valid, so the marriage cannot be performed either at the Office of Religious Affairs (KUA) for those who are Muslim and the Civil Registry Office (KCS) for those who are not Muslim.The legal consequences of illegitimate marriages that are only carried out traditionally by the Lundayeh Dayak have an impact on the absence of recognition from the State for the marriage carried out, so that in the event of a dispute and dispute arising from the marriage, the State in this case the court cannot resolve the dispute resolution. settlement of marital disputes that are only carried out by custom, by the Lundayeh Dayak community carried out in local wisdom, namely through the customary court session Keywords: Marriage, Adat, Dayak Lundayeh